STATUS OF POPULATION, OCCUPATION AND SEASONAL HABITAT DISPLACEMENT OF ALIEN BIRD SPECIES IN WEST JAVA TROPICAL FOREST, INDONESIA - Adiana, Ghazali; Ireana Yusra, Abdul Fatah; Roslan, Umar (2018)
“Invasive Species” is defined as an alien species that is non-native (non-indigenous, foreign or exotic) to a particular ecosystem. Commonly, they are intentionally or unintentionally introduced into an ecosystem. It is suspected that the discovery of a population of Finch-billed Myna in the forest of West Java resulted from the indirect influence of the bird trade. This bird is one of the endemic birds in Indonesia. Commonly, the Finch-billed Myna is a resident bird in Sulawesi islands. However, we found them in Tangkuban Parahu Mount, West Java. The population of Finch-billed Myna in Tangkuban Parahu Mount is 17-24 individual of three group colonies.